The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/sim.3906
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for misclassification for a monotone disease process with an application in dental research

Abstract: Motivated by a longitudinal oral health study, we evaluate the performance of binary Markov models in which the response variable is subject to an unconstrained misclassification process and follows a monotone or progressive behavior. Theoretical and empirical arguments show that the simple version of the model can be used to estimate the prevalence, incidences, and misclassification parameters without the need of external information and that the incidence estimators associated with the model outperformed app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…It is important to stress that in a longitudinal setting, unlike cross sectional studies, the model parameters might be estimated without the use of external information about the misclassification parameters. For instance, García-Zattera et al (2010) showed that under simple restrictions on the parameter space, the model parameters associated with an inhomogeneous HMM for monotone responses are identified by the available data. They also proposed a univariate model to account for predictors allowing for irregularly spaced time intervals and different classifiers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to stress that in a longitudinal setting, unlike cross sectional studies, the model parameters might be estimated without the use of external information about the misclassification parameters. For instance, García-Zattera et al (2010) showed that under simple restrictions on the parameter space, the model parameters associated with an inhomogeneous HMM for monotone responses are identified by the available data. They also proposed a univariate model to account for predictors allowing for irregularly spaced time intervals and different classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Hidden Markov models (HMM) for the analysis of misclassified alternating longitudinal responses has been considered in the literature by Cook, Ng, and Meade (2000), Rosychuk and Thompson (2001), Rosychuk and Thompson (2003), Nagelkerke, Chunge, and Kinot (1990), and Rosychuk and Islam (2009), whereas Espeland, Murphy, and Leverett (1988), Espeland, Platt, and Gallagher (1989), Schmid, Segal, and Rosner (1994), Singh and Rao (1995), Albert, Hunsberger, and Biro (1997), and García-Zattera et al (2010) addressed the problem of misclassified monotone longitudinal responses. It is important to stress that in a longitudinal setting, unlike cross sectional studies, the model parameters might be estimated without the use of external information about the misclassification parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Label uncertainty has commonly been found in clinical judgments due to expert subjectivity and inadequate information [104]. Often, it is handled as noise, so the task has been to detect and correct such mislabeling [87,107,45]. However, in the case of multiple, non-exclusive medical conditions [82], such as comorbidity, it makes more sense to treat labels with degrees of certainty rather than forcing them to belong to one "true" class, because there is no such thing as a single true class in this kind of scenario.…”
Section: Label Characteristicsmentioning
confidence: 99%
“…Such noise is usually regarded as mislabeling to be detected and corrected [87,107,45]. For example, Garca-Zattera et al employed binary Markov 2.2 DATA MINING ON HEALTHCARE DATA 25 models to estimate misclassification parameters for dental research [45].…”
Section: Classification With Label Uncertaintymentioning
confidence: 99%